De-escalation of commitment management strategy in IT project management methodology: case of ERP implementation project by IT consulting company - Zelinskaya, Anna (My University, 2012)
According to several surveys and observations, the percentage of successfully conducted IT projects without over-budgeting and delays in time schedule are extremely low. Many projects also are evaluated as failures in terms of delivered functionality. Nuldén (1996) compares IT projects with bad movies; after watching for 2 hours, one still tries to finish it even though one understands that it is a complete waste of time. The argument for that is 'I've already invested too much time to terminate it now'. The same happens with IT projects: sometimes the company continues wasting money on these projects for a long time, even though there are no expected benefits from these projects. Eventually these projects are terminated anyway, but until this moment, the company spends a lot. The situation described above is a consequence of “escalation of commitment” - project continuation even after a manager receives negative feedback of the project’s success probability. According to Keil and Mähring (2010), even though escalation can occur in any type of project, it is more common among complex technological projects, such as IT projects. Escalation of commitment very often results in runaway projects. In order to avoid it, managers use de-escalation strategies, which allow the resources to be used in more effective. These strategies lead to project termination or turning around, which stops the flow of wasted investments. Numbers of researches explore escalation of commitment phenomena based on experiments and business cases. Moreover, during the last decade several frameworks were proposed for de-escalation strategy. However, there is no evidence of successful implementation of the de-escalation of commitment strategy in the literature. In addition, despite that fact that IT project management methodologies are widely used in the companies, none of them cover the topic of escalation of commitment risks. At the same time, there are no researches proposing the way to implement de-escalation of commitment strategy into the existing project management methodology The research is focused on a single case of large ERP implementation project by the consulting company. Hence, the main deliverables of the study include suggestions of improvement in de-escalation methods and techniques in the project and in the company. Moreover, the way to implement these methods into existing project management methodology and into the company general policies is found.